1213 Vitamin D surveillance in children with down's syndrome in a regional disability service in Dublin. (17th August 2022) - Harte, Shauna; Slattery, Suzanne; Barry, Rachel; McBrien, Jacqueline
Abstract : Aims: Down Syndrome (DS) is the most prevalent chromosomal abnormality in Ireland at 20.70 per 10000 live births 1 . Children with DS are at higher risk of bone health co-morbidities 2 . Severe vitamin D deficiency results in reduced calcium absorption which can manifest as nutritional rickets, hypocalcemia and growth disturbance in the paediatric population 3 . Currently there are no international guidelines for the surveillance of Vitamin D deficiency in DS. The aim of this study was to examine Vitamin D status in a cohort of children with DS attending a Dublin disability service. The research population were all children with DS who have lived in a defined geographical location between 2002 -2020. A secondary aim was to provide evidence to inform practice for the optimisation of Vitamin D status in patients with DS. Methods: A retrospective cohort study on all children with DS attending a large disability service in Dublin (2002-2020). Ethical approval was obtained. The data was extracted from the medical notes and cross referenced with laboratory results. Collected data included: All vitamin D levels recorded in (nmol/L), ethnicity, gender, date of first check, month of the year, calcium, phosphate and parathyroid hormone levels. We classified a Vitamin D level of <50nmol/L as insufficient and a level <30 as deficient. Results: A total of 102 patients with DS were identified in the cohort.60% of the patients were male (n=62). 17% of children in the cohort had a Vitamin D level recorded<50nmol/L (n=18) and 5% had a level<30nmol/L (n=6). Of those deficient/insufficient 25% were female (n=6) and 75% male (n=18). The difference between genders was not found to be statistically significant. In the 0-10 group 12% (n=7) had a level < 50nmol/L and 2% had level <30nmol/L (n=1). In the 10-20 group 25% had level <50nmol/L (n=11) and 11% had level <30nmol/L (n=5). The differences between the two groups in both <50 and <30 category were not statistically significant p=0.1893 and p= 0.3786 respectively. Of the children with Vitamin D< 50nmol/L, 48% (n=12) were recorded in Winter (December –February).Calcium levels were within normal range in all patients. Phosphate levels were low in 2% (n=3) and one of these was linked with insufficient vitamin D levels. Conclusion: Adequate guidance for Vitamin D surveillance in DS is lacking. There were a significant number of children in our cohort identified as deficient. The need for a standardised protocol for the surveillance of Vitamin D in DS was identified and will be re-audited when in place. References: Eu-rd-platform.jrc.ec.europa.eu. European Platform on Rare Disease Registration . [online] Available at: https://eu-rd-platform.jrc.ec.europa.eu/eurocat/eurocat-data/prevalence_en. Bastola, P. and Albert, D., 2018. How Does Down Syndrome Affect Musculoskeletal Health? - The Rheumatologist . [online] The Rheumatologist. Available at: https://www.the-rheumatologist.org/article/how-does-down-syndrome-affect-musculoskeletal-health/?singlepage=1&theme=print-friendly. Munns CF, Shaw N, Kiely M, Speaker BL, Thacher TD, Onzono K et al. Global concensus recommendations on prevention and management of nutritional rickets. Horm Res Paediatrics 2016;85(2) 83-106.